An Integrated Model to Improve Medication Reconciliation in Oncology: Prospective Interventional Study - Alessandro Passardi; Patrizia Serra; Caterina Donati; Federica Fiori; Sabrina Prati; Roberto Vespignani; Gabriele Taglioni; Patrizia Farfaneti Ghetti; Giovanni Martinelli; Oriana Nanni; Mattia Altini; Giovanni Luca Frassineti; et al. (JMIR Publications, 2021)
BackgroundAccurate medication reconciliation reduces the risk of drug incompatibilities and adverse events that can occur during transitions in care. Community pharmacies (CPs) are a crucial part of the health care system and could be involved in collecting essential information on conventional and supplementary drugs used at home. ObjectiveThe aim of this paper was to establish an alliance between our cancer institute, Istituto Romagnolo per lo Studio dei Tumori (IRST), and CPs, the latter entrusted with the completion of a pharmacological recognition survey. We also aimed to integrate the national information technology (IT) platform of CPs with the electronic medical records of IRST. MethodsCancer patients undergoing antiblastic treatments were invited to select a CP taking part in the study and to complete the pharmacological recognition step. The information collected by the pharmacist was sent to the electronic medical records of IRST through the new IT platform, after which the oncologist performed the reconciliation process. ResultsA total of 66 CPs completed surveys for 134 patients. An average of 5.9 drugs per patient was used at home, with 12 or more used in the most advanced age groups. Moreover, 60% (80/134) of the patients used nonconventional products or critical foods. Some potential interactions between nonconventional medications and cancer treatments were reported. ConclusionsIn the PROF-1 (Progetto di Rete in Oncologia con le Farmacie di comunità della Romagna) study, an alliance was created between our cancer center and CPs to improve medication reconciliation, and a new integrated IT platform was validated. Trial RegistrationClinicalTrials.gov NCT04796142; https://clinicaltrials.gov/ct2/show/NCT04796142